Knitted gifts for all seasons : easy projects to make and share - Bernard, Wendy (Wendy Jo) (Abrams, 2021)
"An exciting book from Wendy Bernard, Knitted Gifts for All Seasons is packed with 30 new garments and accessories. Projects are organized by season and range from cozy slippers, mittens, and a pom-pom wreath to Fair Isle yoke-neck sweaters for the whole family. Embracing the full calendar year and a wide spectrum of reasons to gift knits, each project captures the season's essence through color scheme and project type, resulting in a well-rounded and unique book."--Amazon.